Teatcups with automatic valves in machine milking of goats. Issue 1 (22nd September 2017) - Manzur, Alberto; Díaz, José Ramón; Fernández, Nemesio; Balasch, Sebastià; Peris, Cristòfol
Abstract : This Research Paper addresses the hypothesis that using teatcups with automatic valves, without cutting off the vacuum prior to cluster removal, could increases the risk of mastitis and affect other milking variables on goats. A first trial used 46 intramammary infection (IMI)-free goats that had been milked with normal teatcups (without automatic valves) during a pre-experimental period of 8 ± 2 d postpartum. These animals were divided into two groups ( n = 23), randomly assigning each group to teatcups with automatic valves (teatcups A ) or without automatic valves (teatcups B ) for a 20-week experimental period. During this period, several strategies were applied to increase teat exposure to pathogens in both experimental groups. In the first eight weeks of the experimental period, the new IMI rate per gland was significantly higher ( P < 0·05) in the group of animals milked with teatcups A (6 of 46; 13%) than in the group milked with teatcups B (1 of 46; 2%). However, throughout the rest of the experimental period the same number of glands appeared with new IMI ( n = 7) in both animal groups. SCC was higher in goats milked with teatcups A, but no significant differences were found in the remaining variables (milk production and composition, frequency of liner slips + teatcup fall-off). In a second experiment, in a crossover design (54 goats in fourth month of lactation, 2 treatments – teatcups A and B – in 2 experimental periods each lasting 1 week), no differences were observed in total milk, average milk flow, total milking time or teat thickness changes after milking between both teatcups. However, teatcups A worsened slightly the maximum milk flow. We concluded that the use of teatcups with automatic valves, without cutting off the vacuum prior to cluster removal, increases the risk of mastitis on goat livestock farms.